PENDEKATAN PENELITIAN KUANTITATIF DAN KUALITATIF SERTA TAHAPAN PENELITIAN - Risnita Risnita; Muhajirin; Asrulla (Jurnal Genta Mulia, 2024)
Research on holiday meetups is an effort to predict exchanges, conversions, or misunderstandings. However, in order to achieve accurate results, the research setup must use an appropriate approach. The determination of the approach to be used is highly dependent on the researcher's adopted paradigm. This paper discusses the concepts of research paradigms as a foundation for understanding three types of research approaches: quantitative, qualitative, and mixed methods approach.Research that follows the positivism paradigm emphasizes objectivity, while qualitative research represents a naturalistic (phenomenological) approach. The separation between quantitative and qualitative research should not be mixed, but this understanding is often misunderstood by researchers who argue that each approach has its own weaknesses and therefore combining them would enhance the research. The reason for choosing these research approaches is that both types of approaches complement and strengthen each other, resulting in not only objective, structured, and measurable research outcomes, but also in-depth and factual research results.